2017
DOI: 10.1515/popore-2017-0015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the oxidative stress response of two Antarctic fungi to different growth temperatures

Abstract: Two fungal strains, isolated from Livingston Island, Antarctica (Penicillium commune 161, psychrotolerant and Aspergillus glaucus 363, mesophilic) were investigated for a relationship between growth temperature and oxidative stress response. Cultivation at temperatures below -(10 and 15°C and 10 and 20°C for P. commune and A. glaucus, respectively) and above (25°C and 30°C for P. commune and A. glaucus, respectively) the optimum caused significant difference in growth and glucose uptake in comparison with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…Antarctica is isolated geographically from other continents and presents an extremely harsh environment on the earth. Antarctic environment has the characteristics of low temperature, high salinity, low nutrient availability, and strong ultraviolet (UV) radiation [1]. To adapt to the extreme conditions, microorganisms can produce a series of enzymes and display unique metabolic properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antarctica is isolated geographically from other continents and presents an extremely harsh environment on the earth. Antarctic environment has the characteristics of low temperature, high salinity, low nutrient availability, and strong ultraviolet (UV) radiation [1]. To adapt to the extreme conditions, microorganisms can produce a series of enzymes and display unique metabolic properties.…”
Section: Introductionmentioning
confidence: 99%
“…To adapt to the extreme conditions, microorganisms can produce a series of enzymes and display unique metabolic properties. Therefore, Antarctic microorganisms play a crucial part in the field of biomass conversion and have great potential applications, which have aroused more attention [1]. Sea ice is an important component of Antarctic climate and ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, glycogen accumulation seems to be of primary importance for viability at 6°C. Such cold stress response was demonstrated by other fungi and yeasts (Aguilera et al 2007;Gocheva et al 2009;Kostadinova et al 2017). Some studies reported data linking glycogen to microbial viability, suggesting that it is involved in the stress response (Perez-Torrado et al 2002).…”
Section: Discussionmentioning
confidence: 90%
“…In fact, the activation of mechanisms for protection against oxidative stress plays a crucial role in psychrophilic fungi. It has been shown that a cold environment induces the production of reactive oxygen species (ROS), which can cause severe damage to DNA, lipids and proteins, affecting the cell survival (Kostadinova et al ., 2017). The expansion of genes for Zn(2)-C6 transcription factors in C. antarcticus and other psychrophilic extremophiles may help to counter this damage.…”
Section: Discussionmentioning
confidence: 99%